A global comprehensive review of economic interventions to prevent intimate partner violence and HIV risk behaviours - Andrew Gibbs; Jessica Jacobson; Alice Kerr Wilson (Taylor & Francis Group, 2017)
Background: Intimate partner violence (IPV) and HIV are co-occurring global epidemics, with similar root causes of gender and economic inequalities. Economic interventions have become a central approach to preventing IPV and HIV.Objective/Methods: We undertook a comprehensive scoping review of published evaluations of economic interventions that sought to prevent IPV and/or HIV risk behaviours.Results: Forty-five separate analyses of interventions met our criteria. Broadly, unconditional cash transfer interventions showed either flat or positive outcomes; economic strengthening interventions had mixed outcomes, with some negative, flat and positive results reported; interventions combining economic strengthening and gender transformative interventions tended to have positive outcomes.Conclusions: The review highlighted a number of gaps. Specifically, there were limited studies evaluating the impact of economic interventions on female sex workers, young women, and men. In addition, there were missed opportunities, with many evaluations only reporting either IPV- or HIV-related outcomes, rather than both, despite overlaps.